2013
DOI: 10.1136/jnnp-2012-304740
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profiles are associated with lesion formation over 24 months in interferon-β treated patients following the first demyelinating event

Abstract: In early multiple sclerosis, lipid profile variables particularly LDL-C and TC levels are associated with inflammatory MRI activity measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 39 publications
5
103
5
1
Order By: Relevance
“…One possible explanation for this discrepancy is the presence of age-related vascular lesions without central veins. This finding, which remains to be confirmed, supports the contribution of comorbidities to the brain lesion load in patients with MS 36,37 . To date, no imaging studies have been performed on the venocentric distribution of brain lesions in paediatric MS. Susac syndrome.…”
Section: The Central Vein In Ms Discussionsupporting
confidence: 66%
“…One possible explanation for this discrepancy is the presence of age-related vascular lesions without central veins. This finding, which remains to be confirmed, supports the contribution of comorbidities to the brain lesion load in patients with MS 36,37 . To date, no imaging studies have been performed on the venocentric distribution of brain lesions in paediatric MS. Susac syndrome.…”
Section: The Central Vein In Ms Discussionsupporting
confidence: 66%
“…We found that each 10 mg/dl of greater baseline LDL cholesterol (LDL-C), total cholesterol (TC), and apoB was associated with a 7.4%, 5.9%, and 16% increase in the number of new T2 lesions over 2 years of IFN- treatment, respectively (22,23). Our findings on cholesterol and apolipoproteins in MS disease progression have since been independently confirmed (24)(25)(26).…”
Section: Discussionmentioning
confidence: 58%
“…In this report, we investigated the effects of long-term IFN-1a treatment on cholesterol profiles following the first demyelinating event in patients enrolled in the SET study (23,(29)(30)(31). IFN- treatment was associated with an IFN- remains an important first-line MS therapy alongside glatiramer acetate.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities linked to dyslipidemia were reported to be associated with increased risk for MS disability progression [8,10]. It has been reported that lipids and Lp-PLA2 activity has modest effects on MS [8,[10][11][12]. However the data in this field is limited to reach an exact conclusion.…”
Section: Introductionmentioning
confidence: 72%
“…The differences among studies are likely to depending on the genetic, environmental and nutritional factors. The study made by Weinstock et al [12] showed that no associations of LDL-C and total cholesterol with disability changes in patients with high risk clinically isolated syndromes after the first demyelinating event. It was also reported that lipid metabolism in the CNS is regulated independently and almost all cholesterol present in total cholesterol, triglyceride, HDL-C, LDL-C, AIP, non-HDL-C and TCHOL/ HDL-C concentrations between patients and healthy control group.…”
Section: Introductionmentioning
confidence: 99%